Ritual Bakar Tongkang: Refleksi Teologis Bagaimana Manusia Menangkap Tawaran Keselamatan Allah - Harsono Harsono (Jurnal Teologi (Journal of Theology), 2019)
The boat burning festival is held in Bagansiapiapi, Rokan Hilir district, Riau province. It is the most popular ritual in this city. Many people from Indonesia and other countries come to this city, to celebrate the ritual and enjoy the event. Actually, this ritual is held more than one month. It begin with the ritual to ask to the God of the Sea to know what the Gods will. After that, the ritual continues with boat building. Thus, the ritual continues at the 15th, 16th and 17th day of the 5th month in Lunar calendar. On the 17th of the 5th month the boat will be paraded and in the place that have been prepared they burn the boat. This ritual is the annual event. The most interesting thing of this ritual is that the ritual is interpreted as a symbol. From the soteriological point of view, this is the symbol of God salvation. They order to God to give the salvation, especially salvation in this world: fortune, harmony, and peacefulness. In addition, in this ritual, they also aware with their sins. Sins can undo their salvation. Therefore, in this ritual they invoke mercy from God and thus God give to them salvation. This research was qualitative research using interview method. The research sample consisted of nine respondents selected by some requirements. These requirements were understanding the ritual, staying in Bagansiapiapi or having an experience to live there, and being involved in the ritual. The data research was obtained through interview. The additional data obtained through library studies, which was conducted through observation using CD and literature reviews.